Horticulture In Romania Case Study: Flowers - A Luxury for Romanians - Mihaela MUNTEANU PILA; Silvius STANCIU (Communications of International Proceedings, 2021)
The paper forwards an analysis of the Romanian flower sector. The production of flowers and ornamental plants is a sector that can bring considerable revenues and has the potential of being a market niche for Romanian farmers. The analysis was conducted based on the information published by the Ministry of Agriculture and Rural Development, the National Institute of Statistics, the European Commission, as well as media publications. The research has highlighted the fact that the Romanian market is dependent on imports, while domestic exports are low both quantitatively and in value. The main intra-Community supplier of flowers in Romania is represented by The Netherlands, and significant quantities being imported from Latin America. The production of flowers in Romania accounts for less than 1% of the production of the European sector, and the per capita consumption is one of the lowest in the region. The decline in domestic production was accelerated by the Covid-19 pandemic and will continue in the absence of a strong support for the sector from the part of officials. The competition of imports, the lack of investments and the black market are among the main factors affecting the Romanian ornamental plants market. Flowers are a luxury product for Romanians, and unfortunately this is also an imported one.
Keywords: flowers and ornamental plants; import; consumption; Romania